2022
DOI: 10.12982/cmujns.2022.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immersion Time in Simulated Body Fluid on Adhesion Strength of Hydrothermally Treated Hydroxyapatite-Titanium Nitride Films on Polyetheretherketones

Abstract: This study sought to investigate the effect of immersion time in simulated body fluid (SBF) on the adhesion strength of hydrothermally treated hydroxyapatite-titanium nitride (HA-TiN) films on polyetheretherketone (PEEK) substrates. The HA-TiN films were deposited on PEEK substrates via magnetron sputtering and annealed with hydrothermal treatment. The crystalline phase and element compositions on the deposited films were confirmed by X-ray diffractometry (XRD), and X-ray photoelectron spectrometry (XPS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…After being immersed for 56 days, the coating remained with loose density, as seen in SEM. A previous study found that the adhesion strength of the hydrothermally treated HA-TiN coating was stable for 56 days in SBF solution [47], which corresponded with the fact that our coatings remained until the end of immersion at 56 days.…”
Section: Discussionsupporting
confidence: 78%
“…After being immersed for 56 days, the coating remained with loose density, as seen in SEM. A previous study found that the adhesion strength of the hydrothermally treated HA-TiN coating was stable for 56 days in SBF solution [47], which corresponded with the fact that our coatings remained until the end of immersion at 56 days.…”
Section: Discussionsupporting
confidence: 78%